Traumatic Wound Dehiscence 14 Years following Penetrating Keratoplasty. - Maheshwari Sejal (Indian Journal of Ophthalmology, 2003)
Penetrating keratoplasty eyes are at greater risk of laceration than intact corneas due to persistent wound weakness, even years after surgery. We report a case of traumatic wound dehiscence by fingertip injury 14 years following penetrating keratoplasty.